Mekanisme Penggantian Sertipikat Hak Milik yang Rusak di Kabupaten Tabanan - Gede Teguh Rendra Pramudawardana; Ni Putu Sawitri Nandari; Putu Eva Ditayani Antari; Anak Agung Ayu Intan Puspadewi (Jurnal Media Administrasi, 2026)
Land tenure through certificates as valid proof of rights had been recognized, yet in practice damaged certificates still caused administrative obstacles at the BPN of Tabanan Regency. The objective of this research was to analyze the mechanism of replacing damaged Certificates of Ownership and to identify the inhibiting factors in the process. This research used an empirical legal method (socio-legal research) with statutory, conceptual, and factual approaches. Data were collected through interviews with officials at the Tabanan Land Office and literature studies from legal documents and academic sources. The findings showed that the replacement mechanism started with application submission, data matching with the land book, a 30-day public announcement period, field verification including re-measurement if physical data could not be read, and issuance of a replacement certificate directed toward an electronic system. The study also found that the main inhibiting factors included administrative constraints, incomplete documents, unclear legal subjects, potential land disputes, low public understanding, and limited digitalization. These findings indicated that although the mechanism had been regulated, its implementation still faced obstacles affecting legal certainty and service effectiveness. This research implied the need to improve services, legal awareness, and digital transformation.